ANALISIS SARANA PROMOSI MEDIA SOSIAL DAN E-WOM SEBAGAI DIGITAL MARKETING YANG EFEKTIF BAGI DUNIA BISNIS DI ERA SOCIETY 5.0 - Ritonga, Erliana; Harahap, Aziddin; Pristiyono, Pristiyono (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2023)
The concept of digital marketing makes it easier for companies to market their products and services through websites, blogs and social media and even electronic word of mouth (e-WoM). The purpose of this study was to analyze the effect of digital marketing, social media promotion and e-WOM on purchasing decisions. The sample was determined as many as 200 samples taken by purposive sampling (online or online shopping experience). The data analysis technique uses SEM-PLS with the SmartPLS v.4.0 application. The results of the research found showed that demographically the majority of respondents' profiles based on gender, age and occupation were dominated by millennials. Digital marketing and social media promotion have a positive and significant effect on purchase decisions. While the e-WOM variable has no effect on purchasing decisions